Polypharmacy in patients with advanced cancer and the role of medication discontinuation. Issue 7 (July 2015) - LeBlanc, Thomas W; McNeil, Michael J; Kamal, Arif H; Currow, David C; Abernethy, Amy P
Summary Polypharmacy is a well known problem in elderly patients in general, but its prevalence and effects in patients with cancer are less clear, particularly in end-of-life settings. This Review examines the existing literature on polypharmacy in advanced cancer and end-of-life settings by reviewing evidence-based approaches to reduce polypharmacy, and outlining the potential benefits of decreasing the number of drugs that patients with cancer can take, with emphasis on the need for thoughtful discontinuation initiatives in the context of life-limiting malignant disease. In view of the apparent burden of polypharmacy in patients with advanced cancer, we expect that greater attention to polypharmacy could lead to improvements in adverse drug events, cost, and possibly quality of life. However, few data for specific interventions in the advanced cancer population are available, and thus more research is warranted.